En bloc resection and reconstruction of a huge chondrosarcoma involving multilevel upper thoracic spine and chest wall: case report - Xiaodong Tang; Zhenyu Cai; Ruifeng Wang; Tao Ji; Wei Guo (BMC Musculoskeletal Disorders, 2021)
Abstract Background En bloc resection of malignant tumors involving upper thoracic spine is technically difficult. We surgically treated a patient with grade 2 chondrosarcoma involving T1–5, left upper thoracic cavity, and chest wall. Case presentation A 37 years old, male patient was referred to our hospital for a huge lump involved left shoulder and chest wall. In order to achieve satisfied surgical margins, anterior approach, posterior approach, and lateral approach were carried out sequentially. After en bloc tumor resection, the upper thoracic spine was reconstructed with a 3D-printed modular vertebral prosthesis, and the huge chest wall defect was repaired by a methyl methacrylate layer between 2 pieces of polypropylene mesh. Postoperatively, the patient suffered from pneumonia and neurological deterioration which fully recovered eventfully. At 24 months after operation, the vertebral prosthesis and internal fixation were intact; there was no tumor local recurrence, and the patient was alive with stable pulmonary metastases. Conclusion This case report describes resection of a huge chondrosarcoma involving not only multilevel upper thoracic spine, but also entire left upper thoracic cavity and chest wall. Although with complications, en bloc tumor resection with combined surgical approach and effective reconstructions could improve oncologic and functional prognosis in carefully selected spinal tumor patients.